2004
DOI: 10.1007/s00425-004-1373-8
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical consequences of remodeling the neutral side chains of rhamnogalacturonan�I in tubers of transgenic potatoes

Abstract: Two lines of transgenic potato (Solanum tuberosum L.) plants modified in their cell wall structure were characterized and compared to wild type with regard to biomechanical properties in order to assign functional roles to the particular cell wall polysaccharides that were targeted by the genetic changes. The targeted polymer was rhamnogalacturonan I (RG-I), a complex pectic polysaccharide comprised of mainly neutral oligosaccharide side chains attached to a backbone of alternating rhamnosyl and galacturonosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 49 publications
(50 reference statements)
4
73
1
Order By: Relevance
“…We previously inferred that in T13.1, a slowly relaxing component had been lost (Ulvskov et al, 2005). Our relaxation spectra here confirm this, indicating that in T13.1, a component with a t value of around 1,000 s is greatly reduced.…”
Section: Rheological Changes In Tissues With Modified Wall Polymerssupporting
confidence: 85%
See 3 more Smart Citations
“…We previously inferred that in T13.1, a slowly relaxing component had been lost (Ulvskov et al, 2005). Our relaxation spectra here confirm this, indicating that in T13.1, a component with a t value of around 1,000 s is greatly reduced.…”
Section: Rheological Changes In Tissues With Modified Wall Polymerssupporting
confidence: 85%
“…Eliminating side chains would then increase these associations and stiffen the wall, as indicated for arabinan side chains by Jones et al (2003) for stomatal guard cell walls, and as our previous experiments suggested (Ulvskov et al, 2005). Wild-type component(s) with t values approximately 1,000 s would, in T13.1, have become immobile enough that their relaxation lies beyond the upper t limit of our spectrum's reliable range.…”
Section: Rheological Changes In Tissues With Modified Wall Polymerssupporting
confidence: 54%
See 2 more Smart Citations
“…However, the recent finding by Zykwinska et al (2005) that both galactan and to a lesser extent arabinan side chains of RG-I bind specifically to cellulose lead the authors to propose a CW model in which the cellulose microfibrils are tethered by parallel networks of hemicellulose and pectin. The significance of RG-I side chains to physical wall properties have been shown by Jones et al (2003) and Ulvskov et al (2005). The structural significance of RG-II to CW integrity and cell-cell adhesion is well established, and the measurements of tensile strength of wild-type and mutant CWs by Ryden et al (2003) showed that both xyloglucan cross-linking and RG-II borate complex formation are essential for wall strength.…”
Section: Discussionmentioning
confidence: 99%